Роздрібна торгівля продуктами харчування в Україні: сучасний стан та виклики - Пєтухова, Ольга Михайлівна; Закревська, Людмила Миколаївна (My University, 2023)
Стаття присвячена дослідженню сучасного стану роздрібної торгівлі продуктами харчування в Україні та розробленню напрямів протидії сучасним економічним викликам у сфері ритейлу. Визначено вплив роздрібної торгівлі продуктами харчування на грошовий оборот країни. Визначено сутність поняття «продукти харчування» та його відмінність від харчових продуктів. Доведено, що динаміка обсягів продажу продуктів харчування має циклічний характер. Проаналізовано структуру вітчизняного товарообороту роздрібної торгівлі за групами продуктів харчування та виявлено наявність «відкладеного» попиту на фрукти та овочі, рибу та рибні вироби. Досліджено динаміку обсягів товарообороту за групами продуктів харчування в 2017–2021 рр. Виявлено вплив карантинних обмежень на зміну динаміки товарообороту та методів просування товарів в сфері роздрібної торгівлі продуктами харчування. The article is devoted to the study of the current state of food retail trade in Ukraine and the develop- ment of countermeasures to modern economic challenges in the retail sector. The impact of food retail trade on the country's monetary turnover is determined. The essence of the concept of "food products" and its difference from food products is defined. It has been proven that food products should be understood as food products for consumption by humans and other living beings. It has been proven that the dynamics of sales volumes of food products is cyclical in nature. The dynamics of sales vol- umes of food products in Ukraine through cash registers were analyzed and a significant reduction in sales of this product group was determined. The continuation of this negative dynamic in the future is predicted by constructing a linear regression equation. The structure of domestic retail turnover by food product groups was analyzed and the presence of "delayed" demand for fruits and vegetables, fish and fish products was revealed. It was determined that the deterioration of the economic situation and a decrease in the income of citizens may lead to a redistribution of sales of alcoholic products within the category towards cheaper ones. The dynamics of merchandise turnover by food product groups in 2017–2021 were studied. The main reasons for the increase in merchandise turnover by all food product groups were attributed to a significant increase in the price of fuel and lubricants. Due to sup- ply problems and inflationary pressures, food prices are forecast to rise in the future. The influence of quarantine restrictions on the change in the dynamics of turnover and methods of product promotion in the field of food retail trade has been revealed. This is a consequence of the COVID-19 coronavi- rus pandemic. It found that during the pandemic, many food retailers began to pay more attention to maintaining close ties with suppliers to strengthen supply chains. It has been proven that ensuring the effective functioning of food retail trade facilities can be achieved by maximally meeting the needs of consumers and minimizing time spent.
Keywords: кафедра маркетингу; кафедра економіки і права; роздрібна торгівля; обсяг роздрібного обороту; роздрібний товарооборот; продукти харчування; харчові продукти; retail trade; volume of retail turnover; retail turnover; food products